2013
DOI: 10.1021/bc400032x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling, Amphiphilic Polymer–Gemcitabine Conjugate Shows Enhanced Antitumor Efficacy Against Human Pancreatic Adenocarcinoma

Abstract: The therapeutic efficacy of gemcitabine is severely compromised due to its rapid plasma metabolism. Moreover, its hydrophilicity poses a challenge for its efficient entrapment in nanosized delivery systems and to provide a sustained release profile. In this study, gemcitabine was covalently conjugated to poly(ethylene glycol)-block-poly(2-methyl-2-carboxyl-propylene carbonate) (PEG-PCC) which could self-assemble into micelles of 23.6 nm. These micelles afforded protection to gemcitabine from plasma metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 51 publications
3
114
0
Order By: Relevance
“…Therefore, in this study, we conjugated DTX and CYP to a biodegradable amphiphilic diblock copolymer mPEG-b-PCC with pendant carboxyl acid groups. We previously conjugated a water soluble drug gemcitabine as well as dodecanol to mPEG-b-PCC, which self-assembled into micelles and showed enhaced drug delivery to pancreatic tumor, which resulted in significant reduction in tumor growth [2022]. In this study, DTX was conjugated to mPEG-b-PCC through an ester bond at its 2′-OH position.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, we conjugated DTX and CYP to a biodegradable amphiphilic diblock copolymer mPEG-b-PCC with pendant carboxyl acid groups. We previously conjugated a water soluble drug gemcitabine as well as dodecanol to mPEG-b-PCC, which self-assembled into micelles and showed enhaced drug delivery to pancreatic tumor, which resulted in significant reduction in tumor growth [2022]. In this study, DTX was conjugated to mPEG-b-PCC through an ester bond at its 2′-OH position.…”
Section: Discussionmentioning
confidence: 99%
“…Mahato and co-workers, for example, conjugated Gem and dodecanol (C 12 H 25 OH) to a PEG- b -PCC (poly(2-methyl-2-carboxyl-propylene carbonate) polymer through amide and ester linkages, respectively (Figure 5a). 67 This conjugate formed spherical micelles averaging 24 nm in diameter and with a drug loading of almost 13%. In vivo studies indicated a significant increase in effectiveness over free Gem.…”
Section: Macromolecular Sapdsmentioning
confidence: 99%
“…micelles), which is critical for deep tumor permeation of the pancreas, 8 controllable release of GEM, and active tumor targeting via the installation of tumor targeting ligands. [9][10][11][12][13][14][15] Recently, photothermal therapy (PTT) has shown great potential in cancer treatment. 16 PTT comprises the thermal ablation of cancer cells using a red/near-infrared (NIR) laser photoabsorber such as noble metal nanostructures, 17,18 transition metal sulphides/oxides nanomaterials 19,20 and other nanoagents.…”
Section: Introductionmentioning
confidence: 99%